Developing Mothers' Knowledge about Weaning Food in Infants Aged 6-24 Months through Video - Sari, Dian Vita; Khalsiah, Khalsiah; Fatmawati, Fatmawati; Ahmady, Dedy; Sari, Maulida; Ardilla, Arista; Zulkarnaini (Babali Publisher, 2024)
Background: During this period, infants and children receive food and drink with an appropriate nutritional intake for optimal growth and development. Media such as audiovisual videos make it easier to increase maternal knowledge. This study was conducted to determine the effect of video on rising mothers' knowledge about weaning food in infants 6-24 months at Posyandu (Integrated Service Center). Methods: The type of research was quantitative, which is experimental with a one-group pre-post-test design approach. This study's population was mothers with children aged 6-24 months, using the total sampling method. Data collection used a questionnaire as an instrument that contained information on complementary foods. Data analysis used univariate and bivariate analysis with the Wilcoxon test. Results: the results showed a significant influence between weaning food education through video about maternal knowledge obtained with p-value=0.001 <a=0.05. Conclusion: There was a significant difference in maternal knowledge before and after being given an educational video intervention on complementary foods, which means that educational video affects increasing maternal knowledge about complementary foods in infants aged 6-26 months in the village.